Study micromixing pada tangki teraduk secara kontinyu - Ali Altway; W Widiyastuti; M Rachimoellah; Sugeng Winardi (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2004)
The aim of this work is to study the influence of micromixing on product distribution for parallel reaction systems in an agitated tank. The understanding of micromixing is needed besides macromixing to obtain the optimum process. The neutralization reaction of NaH2BO3 and oxidation-reduction reaction between lodide-lodate to generate iodine are selected to perform parallel reaction systems. These reactions were conducted in a flat bottom cylindrical tank 0.2 m in diameter (T) at room temperature (30oC) agitated by six blades fan turbine having diameter (Da)=1/3T and impeller width (W)=1/4T. The impeller clearance was I/3H. The height of liquid in the tank is equal to its diameter (H=T). This tank was operated as continuous reactor type. The inf1uences of impeller speed, residence time and feed position were analyzed. Segregation number and the yield of iodine generation determine the micromixing degree and the performance of reactor respectively. The impeller rotation speed was varied 100-300 rpm. The residence time varied 6.01, 4.005 and 3.005 minutes. The feed position was varied on [r